Photo-induced dynamic room temperature phosphorescence based on triphenyl phosphonium containing polymers - Wang, Chang (2022)
Long-lived room temperature phosphorescence (RTP) systems have become a research focus in the field of functional materials due to their fascinating luminescence properties. However, it is still an enormous challenge to realize RTP under ambient conditions, since RTP can be quenched easily by molecular oxygen. Herein, two polymer acceptors containing triphenyl phosphonium bromide salt are designed and synthesized successfully. They are then doped into a poly(methyl methacrylate) matrix with donor molecules to form flexible films with long-lived RTP. Interestingly, the long-lived RTP performance is highly dependent on the grafting rate of the polymers. Upon increasing the grafting rate, the aggregation degree of polymer acceptors increases, further inhibiting the molecular movement in the aggregates and reducing nonradiative vibration deactivation of triplet excitons for achieving green long-lived RTP. Meanwhile, the visualization of real information and complete pattern after 365 nm UV irradiation is demonstrated based on these long-lived RTP systems, presenting application potential toward dynamic multilevel information encryption and display devices. This work provides an innovative principle for the activation of long-lived RTP in the polymeric systems under ambient conditions.